Molecular recognition of an acyl–enzyme intermediate on the lipase B from Candida antarctica - Toledo, María Victoria; Llerena Suster, Carlos Rafael; Ferreira, María L.; Collins, Sebastián E.; Briand, Laura Estefanía (2017)
This investigation provides evidence of the acyl enzyme species involved in the interaction of R/S ketoprofen with the lipase B from Candida antarctica . The interaction between the profen and the enzyme was studied by in situ time-resolved ATR-FTIR under both static and transient conditions. Particularly, modulation excitation spectroscopy (MES) with phase sensitive detection (PSD) allowed us to univocally distinguish the signals belonging to the interaction between ketoprofen and the enzyme from the strong background signals. These experimental tools coupled with theoretical DFT analysis allowed us to propose various species derived from the interaction of ketoprofen with serine through H bonding (without reaction) and the acyl enzyme species (ester bond formation) which are the intermediates in the biocatalytic assisted esterification and hydrolysis using lipases. Centro de Investigación y Desarrollo en Ciencias Aplicadas Facultad de Ciencias Exactas